Investigating the Link Between Macroeconomic Factors and Income Inequality of Asian Countries - Aman, Ameenullah; Ahmad, Usman; Sumera Muhammad Saleem (iRASD Journal of Economics, 2021)
The main purpose of the study was to analyze the impact of macroeconomic factors on income inequality. The panel data analysis is conducted on the sample data of 36 Asian countries. The data of 19 years from the period 2001 to 2019 is collected to analyze the impact of interest rate, economic growth, FDI and exports. The findings revealed the positive relationship between income inequality and economic growth whereas FDI and exports have negative relationship with income inequality. Result of the study implies that authorities should pay special attention to design policies that encourage inward FDI and increase exports.